Mystery, History, Minatory! A Historical Critique on the Book Sapiens; A Brief History of Humankind - Abolhasan Fayaz Anush (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In Sapiens; A Brief History of Humankind by Yuval Noah Harari the 200.000 years of history of sapiens has been presented to the reader as an appendix to the 13.500.000.000 years of the world history. Sapiens covers numerous topics in the fields of humanities and non-humanities. However, considering that the subtitle of the book claims to present human history, this article deals only with the historical critique of this work, that is, the methodological approach and the critique of the author’s historical theory, and will critique the methodological capacities of this book from the perspective of critical philosophy of history and its theoretical discussions from the position of evolutionary creationism. Focusing on the content of the book and the authors method, this article deals with three sections: 1) prehistoric period; from 13.5 billion years ago to the invention of calligraphy in 5.000 years ago 2) historical period; from the invention of calligraphy until now, and 3) posthistoric period; human future. According to the critical view of this article, the words mystery, history and minatory refer to these three periods, respectively.